KAJIAN ASPEK FINANSIAL REHABILITASI MANGROVE DENGAN POLA SILVOFISHERY DI KABUPATEN PEMALANG - Heru Salam (Jurnal Dinamika Sosial Ekonomi, 2005)
The feasibility study of farming system and silvofishery as rehabilitation model of mangrove area was conducted at Pemalang district. Fifty farmers ware sampled purposively. Income analysis is used to determine the farmer income, benefit cost ratio (BCR), net present value (NPV) and internal rate return (IRR) are used to determine the feasibility of silvofishery farming. The community comprehension to function of rehabilitation is analyzed by scoring of Likert scale. The result of analysis indicate that BCR: 1,825 NPV (20%) : Rp 40.541.048, and IRR: 67, 856% and 70% of local community is understood the function of mangrove rehabilitation. It is concluded that silvofishery can be adopted an financially feasible and profitable model of mangrove rehabilitation.Key words: silvofishery, mangrove rehabilitation, and economic aspect